Perspectives on design and digital communication II research, Innovations and best practices - Martins, Nuno; Brandão, Daniel; da Silva, Fernando Moreira (Springer Series in Design and Innovation, 2021)
This book gathers new empirical findings fostering advances in the areas of digital and communication design, web, multimedia and motion design, graphic design, branding, and related ones. It includes original contributions by authoritative authors based on the best papers presented at the 4th International Conference on Digital Design and Communication, Digicom 2020, together with some invited chapters written by leading international researchers. They report on innovative design strategies supporting communication in a global, digital world, and addressing, at the same time, key individual and societal needs. This book is intended to offer a timely snapshot of technologies, trends and challenges in the area of design, communication and branding, and a bridge connecting researchers and professionals of different disciplines, such as graphic design, digital communication, corporate, UI Design and UX design. Chapter “Definition of a Digital Tool to Create Physical Artifacts: The Case of the Gamers4Nature Project” is available open access under a Creative Commons Attribution 4.0 International License via link.springer.com.